Implementasi Manajemen Sekolah Standar Nasional - Sayful Amrin (Ekspektasi: Jurnal Pendidikan Ekonomi, 2017)
The purpose of research to know implementation of National Standard School Management (SSN) in SMP Negeri 2 Ende. The result showed that the implementation of the national standard school program (SSN) at SMP Negeri 2 Ende was implementation well in accordance with the 8 national standards of education (SNP) constaraints encontered with good management ability by the school. The implementation of the national standard school program (SSN) in SMP Negeri 2 Ende can improve the quality of education seen from the data of the last five years graduation with 100%.